2011
DOI: 10.1103/physrevb.83.174431
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale structure of the magnetic induction at monopole defects in artificial spin-ice lattices

Abstract: Artificially frustrated spin-ice systems are of considerable interest since they simulate the spin frustration and concomitant rich behavior exhibited by atoms on a crystal lattice in naturally occurring spin-ice systems such as pyrochlores. As a result of the magnetic frustration these systems can exhibit "magnetic monopole" type defects, which are an example of an exotic emergent quasiparticle. The local magnetization structure of such monopole defects determines their stability and thus is critical to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 21 publications
(11 reference statements)
4
91
0
Order By: Relevance
“…As a result of the magnetic frustration, these systems can exhibit magnetic monopole type states, which are an example of an exotic emergent quasiparticle [280,299,300,301,302,303,304,305,306,307,308,309,310,311]. For example, magnetic monopoles and associated Dirac-like strings have been directly observed in the artificial honeycomb (on Co films of 20 nm thickness) and Kagome spin ice (permalloy films) systems [312,313,314] using magnetic force microscopy and X-ray photoemission microscopy.…”
Section: Artificial Spin Icementioning
confidence: 99%
“…As a result of the magnetic frustration, these systems can exhibit magnetic monopole type states, which are an example of an exotic emergent quasiparticle [280,299,300,301,302,303,304,305,306,307,308,309,310,311]. For example, magnetic monopoles and associated Dirac-like strings have been directly observed in the artificial honeycomb (on Co films of 20 nm thickness) and Kagome spin ice (permalloy films) systems [312,313,314] using magnetic force microscopy and X-ray photoemission microscopy.…”
Section: Artificial Spin Icementioning
confidence: 99%
“…A wide range of interesting behavior 2,3 can be observed in these artificial frustrated magnets by tuning the geometry of square [4][5][6][7] , triangular 8,9 , hexagonal (and kagome) [10][11][12][13][14][15][16][17][18][19][20] and brickwork lattices, as well as isolated clusters 21 . In particular, the local moment behavior of these systems has shown that they are good realizations of ice models, and a range of studies have examined monopole excitations and drawn upon close analogies with the pyrochlore spin ice materials.…”
Section: Figmentioning
confidence: 99%
“…Simple square and kagome artificial spin ice lattices have been subject to intense study because they provide unique insight into the consequences of frustrated magnetism, such as residual entropy 9,10 and magnetic charge excitations [11][12][13][14] . In the last few years, improved thermalization methods have provided access to the low energy phases of artificial spin ice structures 10,15,16 and even their dynamics [17][18][19] .…”
mentioning
confidence: 99%